2014
DOI: 10.1363/46e2514
|View full text |Cite
|
Sign up to set email alerts
|

Planning for Motherhood: Fertility Attitudes, Desires And Intentions Among Women with Disabilities

Abstract: CONTEXT An estimated 10% of U.S. women of reproductive age report a current disability; however, the relationship between disability, motherhood attitudes and fertility intentions among these women is largely unknown. METHODS Data from the 2006–2010 National Survey of Family Growth were used to examine attitudes toward motherhood and fertility intentions among 10,782 U.S. women aged 15–44. A series of regression models assessed, separately for mothers and childless women, associations between disability stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 32 publications
(52 reference statements)
0
34
0
Order By: Relevance
“…Recent evidence suggests that women with and without disabilities were equally likely to want children, but women with disabilities were less certain about their intentions to have children. 17 Findings limited to current pregnancy at time of interview found a lower prevalence of pregnancy among women with chronic physical disabilities compared to those without disabilities, but pregnancy prevalence was similar after adjusting for other socio-demographic characteristics associated with pregnancy. 18 An analysis of data from women with spinal cord injuries found that 2% reported a pregnancy during the past 12 months, similar to the rate of current pregnancy among all women with physical disabilities.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent evidence suggests that women with and without disabilities were equally likely to want children, but women with disabilities were less certain about their intentions to have children. 17 Findings limited to current pregnancy at time of interview found a lower prevalence of pregnancy among women with chronic physical disabilities compared to those without disabilities, but pregnancy prevalence was similar after adjusting for other socio-demographic characteristics associated with pregnancy. 18 An analysis of data from women with spinal cord injuries found that 2% reported a pregnancy during the past 12 months, similar to the rate of current pregnancy among all women with physical disabilities.…”
Section: Introductionmentioning
confidence: 87%
“…15,17 Yet women with disabilities have reported a lack of clear guidance from physicians as to whether or not they can safely have children. 16 There is some evidence among Medicaid recipients that women with disabilities were less likely to receive early and adequate prenatal care than their counterparts without disabilities.…”
Section: Commentmentioning
confidence: 99%
“…Similarly, women with disabilities are often discouraged from having children, due to health concerns and/or beliefs that motherhood and disability are incompatible (Pebdani et al 2013); pregnant women with visible disabilities report experiencing questions, skepticism, and harassment from friends, family, and strangers (Prilleltensky 2003). Yet many women with disabilities are sexually active (Esmail et al 2010; Jahoda and Pownall 2013), wish to become mothers (Shandra et al 2014), and do so (Iezzoni et al 2014), underscoring the need to better understand the reproductive health and needs of women with disability.…”
Section: Introductionmentioning
confidence: 99%
“…A rare exception is one population-based study of fertility attitudes, desire and behavior among women with disabilities compared to those without (Shandra et al 2014). Analyses of these data ( N = 10,782), drawn from the 2006–2010 National Survey of Family Growth (NSFG), found both groups held similar attitudes, desires, and intentions towards motherhood.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy intentions of women with disabilities have only recently been considered in the literature. Two population‐based studies, published in 2014 and 2017, found that women with disabilities were as likely to want a baby as women without disabilities 1,2 . However, women with disabilities were less likely to report actual intentions to have a baby in the future, and were less certain about their childbearing intentions, than women without disabilities 1,2 .…”
mentioning
confidence: 99%